2018
DOI: 10.3892/ol.2018.7772
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 in the microenvironment of HNSCC inhibits the CpG ODN induced IFN-α secretion of pDCs

Abstract: Abstract. It has been shown that head and neck squamous cell carcinoma (HNSCC) is infiltrated by plasmacytoid dendritic cells (pDCs). The HNSCC TH2 biased microenvironment leads to strong alterations of the cellular functions of pDC and thus impairs the initiation and function of adequate immune responses. In this work we comprehensively analyzed the capacity of CpG-oligonucleotides to activate interferon (IFN)-α secretion of human pDC in the presence of HNSCC. IFN-α secretion was measured using the ELISA Tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…The same author group later elucidated the underlying mechanism of impaired IFNα secretion, identifying prostaglandin E2 and TGFβ from HNSCC culture supernatants as the most important negative regulators of pDC functions [50]. Other research teams reported similar effects on IFNα secretion in the setting of HNSCC when blood-derived human pDCs were incubated with tumor supernatants [51,52]. Bruchhage et al also analyzed cytokines in HNSCC supernatants and tested their effect on pDCs.…”
Section: Negative Role Of Pdcs In Solid Tumorsmentioning
confidence: 99%
“…The same author group later elucidated the underlying mechanism of impaired IFNα secretion, identifying prostaglandin E2 and TGFβ from HNSCC culture supernatants as the most important negative regulators of pDC functions [50]. Other research teams reported similar effects on IFNα secretion in the setting of HNSCC when blood-derived human pDCs were incubated with tumor supernatants [51,52]. Bruchhage et al also analyzed cytokines in HNSCC supernatants and tested their effect on pDCs.…”
Section: Negative Role Of Pdcs In Solid Tumorsmentioning
confidence: 99%
“…Of note, head and neck squamous cell carcinoma is infiltrated by B cells (CD19, CD20) producing immunoglobulins and immature pDCs that can produce type I interferons (IFNs), including IFN-α, although why the association to CD19 with FCRLA or CD20 with FCRLA up-regulate the IFN-α, through pDCs, is not clear 39 , 47 , 48 . However, the type I IFNs could have significant antitumor efficacy, beyond the activation of the host innate immune response 49 51 .…”
Section: Discussionmentioning
confidence: 99%
“…pDCs isolated from HNSCC tissues or exposed to HNSCC supernatants show an impaired IFN-α production upon CpG stimulation compared to blood-derived pDCs or pDCs exposed to control medium [131,140,173]. Tumor-induced down-regulation of TLR9 expression has been identified as one leading mechanism of pDC dysfunction within the tumor environment [140,142].…”
Section: The Dual Role Of Pdcs In Human Cancermentioning
confidence: 99%
“…Tumor-induced down-regulation of TLR9 expression has been identified as one leading mechanism of pDC dysfunction within the tumor environment [140,142]. Furthermore, significant levels of PGE2, TGF-β and IL-10 are detected in the HNSCC and OSCC culture supernatants as mediators of IFN-α impairment in pDCs [140,142,161,173]. A decreased secretion of IFN-α, TNF-α, and IL-6 by tumor infiltrating pDCs was also detected in OSCC [141].…”
Section: The Dual Role Of Pdcs In Human Cancermentioning
confidence: 99%